TINJAUAN FIKIH MUAMALAH TERHADAP POLA KERJASAMA TAMBANG EMAS STUDI KASUS DI JORONG TANJUNG BERINGIN, KAB. SIJUNJUNG - Noni Kurnia Esa; Afrian Raus (UIN Mahmud Yunus Batusangkar, 2023)
A study oe the Muamalah fiqh review of gold mining cooperation pattern case studies in jorong tanjung beringin, sijunjung regency. The problem is what contract used and what is the muamalah fiqh review of the pattern of gold mining cooperation. The research was analyzed using a qualitative descriptive method, a type of field research. The cooperation pattern for gold mining results uses a written cooperation agreement. Meanwhile, the nuamalah fiqh review of the collaboration pattern for gold mining profit sharing is in accordance with the muamalah fiqh provisions.where the pillars and conditions of the contract have been fulfilled, namely the existence of a person who is in contract, the existence of land that is used as an object , the existence of consent and qabul and the purpose of the contract being carried out. Cooperation that has been carried out by land owners with investors does not guarantee the fiqg muamalah provisions. Regarding the loss of money in the agreement, it is the willingness of both parties in the contract and that willingness is the basis for the permissibility of the agreement. This is in accordance with surah An-Nisa verse 29.